(1)
在Sn十n=2an中,令n=1得a1+1=2a1所以a1=1
n≥2時
Sn十n=2an
S(n-1)+(n-1)=2a(n-1)
兩式相減得an +1=2an-2a(n-1)
即an -1=2a(n-1)
兩邊同時加上2得an +1=2[a(n-1)+1]
又a1 +1=2≠0
所以an +1≠0
所以(an +1)/[a(n-1)+1]=2
所以{an十1}是以2為首項,2為公比的等比數列
an +1=2×2^(n-1)=2^n
an=2^n -1
(2)bn=n×2^n
Tn=1*2+2*2^2+...+n*2^n
2Tn= 1*2^2+...+(n-1)*2^n+n*2^(n+1)
相減
-Tn=2+2^2+……+2^n-n*2^(n+1)
=2(1-2^n)/(1-2)-n*2^(n+1)
=2^(n+1) -2-n*2^(n+1)
=(1-n)2^(n+1) -2
所以Tn=(n-1)2^(n+1) +2
(1)
在Sn十n=2an中,令n=1得a1+1=2a1所以a1=1
n≥2時
Sn十n=2an
S(n-1)+(n-1)=2a(n-1)
兩式相減得an +1=2an-2a(n-1)
即an -1=2a(n-1)
兩邊同時加上2得an +1=2[a(n-1)+1]
又a1 +1=2≠0
所以an +1≠0
所以(an +1)/[a(n-1)+1]=2
所以{an十1}是以2為首項,2為公比的等比數列
an +1=2×2^(n-1)=2^n
an=2^n -1
(2)bn=n×2^n
Tn=1*2+2*2^2+...+n*2^n
2Tn= 1*2^2+...+(n-1)*2^n+n*2^(n+1)
相減
-Tn=2+2^2+……+2^n-n*2^(n+1)
=2(1-2^n)/(1-2)-n*2^(n+1)
=2^(n+1) -2-n*2^(n+1)
=(1-n)2^(n+1) -2
所以Tn=(n-1)2^(n+1) +2